Situation Report: Romania, 17 July 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Weapons Trade / by Paul Gafton Foreign Students Creating Problems / by Ioana Angelescu The Economy Reflected in a Drop of (Mineral) Water / by Paul Gafton Agricultural Quandary / by Paul Gafton Video Equipment / by Carmen Cojocaru-Pompei Renewed Emphasis on Atheism / by Carmen Cojocaru-Pompei